2019
DOI: 10.1080/10253890.2019.1625885
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive differences in glucocorticoid responsiveness are related to divergent spatial information processing abilities

Abstract: Lay summary: Rats selected for different glucocorticoid responses to stress show differences in spatial learning and cognition. While the high responding animals have a better long-term spatial memory retention, the Low responding rats have an inferior spatial memory and impaired reversal learning abilities.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 75 publications
2
6
0
Order By: Relevance
“…Specifically, animals that showed poorer retention levels on the first trial following training day 1 were the ones that showed blunted corticosterone reactivity when exposed as adults to a novelty challenge. These observations align well with the well-known contribution of training-triggered corticosterone levels for memory function in general (de Kloet et al, 2018; de Quervain et al, 2017; Sandi, 2011)) and, specifically, for the consolidation of spatial information (Akirav et al, 2004; Conboy et al, 2010; Huzard et al, 2020; Quirarte et al, 1997; Sandi et al, 1997).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Specifically, animals that showed poorer retention levels on the first trial following training day 1 were the ones that showed blunted corticosterone reactivity when exposed as adults to a novelty challenge. These observations align well with the well-known contribution of training-triggered corticosterone levels for memory function in general (de Kloet et al, 2018; de Quervain et al, 2017; Sandi, 2011)) and, specifically, for the consolidation of spatial information (Akirav et al, 2004; Conboy et al, 2010; Huzard et al, 2020; Quirarte et al, 1997; Sandi et al, 1997).…”
Section: Discussionsupporting
confidence: 87%
“…Strikingly, individual differences in the adaptation of the glucocorticoid response to repeated stress exposure during the peripubertal period in rats were found to predict subsequent changes in emotional and social phenotypes observed during adolescence (Papilloud et al, 2019) and adulthood (Walker et al, 2018; 2017). In addition, genetic selection in rats for the degree of corticosterone adaptation during peripubertal stress (Walker and Sandi, 2018) underscored genetic line-related differences in spatial learning and memory performance (Huzard et al, 2020). Accordingly, given the strong modulatory capacity of glucocorticoids on brain function and cognition (de Quervain et al, 2017; Sandi, 2011), including spatial learning (Akirav et al, 2004; Conboy et al, 2010; Sandi et al, 1997), we hypothesize that long-term programming of peripubertal stress on spatial learning would depend on the individual degree of glucocorticoid adaptation to repeated stress.…”
Section: Introductionmentioning
confidence: 99%
“…While the exact nature and mechanisms for aging continue to be debated, important markers of biological age might include blood measures of genomic instability, epigenetics, and cellular senescence (Lidzbarsky et al, 2018;Niedernhofer et al, 2018;Aristizabal et al, 2020), telomere length (Vera et al, 2013;Stauffer et al, 2018), inflammation and the proinflammatory secr, etory profile designated the senescence-associated secretory phenotype (SASP;Boersma et al, 1985;Heller et al, 1998;Guayerbas et al, 2002;Moeller et al, 2014;Martinez de Toda et al, 2016), hormone levels (Gee et al, 1983;Matt et al, 1986;Smith et al, 1992;Fentie et al, 2004), mitochondrial function, redox state, and antioxidant defense (Heller et al, 1998;Stauffer et al, 2018;Jain et al, 2019). For example, levels of corticosterone in the blood have been associated with memory function during aging (McQuail et al, 2018;Huzard et al, 2020).…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…Will we observe the same trajectory classes in other AAPA experiments, depending on the treatments and with other strains? Our earlier work on MWM and the strategies identified therein were in fact used to analyse data from different experiments and labs 24 , 29 , 30 , suggesting that it might be possible that the same generality holds for the AAPAT. However, we need to highlight a fundamental difference.…”
Section: Discussionmentioning
confidence: 99%